2020
DOI: 10.3906/sag-1807-230
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of treatment efficacy of diphenylcyclopropenone (DPCP) for alopecia areata

Abstract: Background/aim: Alopecia areata is an inflammatory disease with a genetic and autoimmune basis. We aimed to study the efficacy, and safety of an immunomodulatory therapeutic agent, diphenylcyclopropenone, while manifesting the association with histopathological features, prognostic factors and side effects. Materials and Methods: In this retrospective study, 98 patients (60 men, 38 women) with alopecia who were referred to the "Hair Disease Polyclinic" at Department of Dermatology between 2011 and 2015 were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…9 Although the exact mechanism of topical immunotherapy on AA remains unknown, an immunomodulatory effect on inflammatory infiltration around the hair follicle is considered to play a role. 5,8,9 DPCP is an experimental sensitizing agent for topical immunotherapy that is most often used to treat AA. 8 However, there is a risk associated with the use of DPCP in AT patients with AD in that DPCP can exacerbate AD by inducing a nonspecific allergic reaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Although the exact mechanism of topical immunotherapy on AA remains unknown, an immunomodulatory effect on inflammatory infiltration around the hair follicle is considered to play a role. 5,8,9 DPCP is an experimental sensitizing agent for topical immunotherapy that is most often used to treat AA. 8 However, there is a risk associated with the use of DPCP in AT patients with AD in that DPCP can exacerbate AD by inducing a nonspecific allergic reaction.…”
Section: Discussionmentioning
confidence: 99%
“…5,8,9 DPCP is an experimental sensitizing agent for topical immunotherapy that is most often used to treat AA. 8 However, there is a risk associated with the use of DPCP in AT patients with AD in that DPCP can exacerbate AD by inducing a nonspecific allergic reaction. Patients with severe AD with many T cells activated, including T helper 2 cells, may experience severe systemic nonspecific allergic reactions even in DPCP sensitization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Marmesin, as a natural furan coumarin compound, has the functions of anti-aging, 22 antifungal, 23,24 inhibiting the proliferation of vascular endothelial cells and protecting vascular endothelium. 25 Diphenylcyclopropenone (DPCP) is a topical immune response modifier, which induces contact dermatitis with DPCP and leads to hair regeneration, so it is used in the study of alopecia areata, 26,27 the study showed that DPCP can effectively treat patients with alopecia areata via TSLP/OX40L/IL-13 pathway. 28 Angelic Acid is a substance in the essential oil of Anthemis nobilis, which is helpful for wound healing and has sedative properties as psychotropic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In 10 selected studies, side effects from DPCP were not mentioned, although some studies have shown good results with acceptable side effect profiles (36). In 2020, a study conducted by Kutlubay, children over 5 years of age were also included and the treatment results or safety parameters were similar to those of the adult patients (37).…”
Section: Discussionmentioning
confidence: 99%